Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to find the sum of :

$$\sum_{i=1}^n\ \frac i {2^i}$$

I've tried to run $i$ from $1$ to $∞$ , and found that the sum is $2$ , i.e :

$$\sum_{i=1}^\infty\ \frac i {2^i} =2$$

since :

$$(1/2 + 1/4 + 1/8 + \cdots) + (1/4 + 1/8 + 1/16 +\cdots) + (1/8 + 1/16 + \cdots) +\cdots = 1+ 1/2 + 1/4 + 1/8 + \cdots = 2 $$

But when I run $i$ to $n$ , it's a little bit different , can anyone please explain ?

Regards

share|improve this question
    
When you sum till $n$, the left hand side of your last displayed equation is the sum of $n$ geometric series that grow shorter and shorter. Use the formula for the sum of a finite geometric series on each of the $n$ series, and then sum the sums. –  Dilip Sarwate Apr 8 '12 at 13:29
1  
You could also try differentiating $\sum x^{n + 1}$ term by term. Then you will find an expression for $\sum n x^{n}$. Set $x = \frac{1}{2}$ –  Pedro Apr 8 '12 at 13:32
1  

3 Answers 3

up vote 5 down vote accepted

For the sake of generality, and more importantly to make typing easier, we use $t$ instead of $1/2$. We want to find the sum $$S(t)=t+2t^2+3t^3+4t^4+ \cdots +(n-1)t^{n-1}+nt^n.$$ Multiply both sides by $t$. We get $$tS(t)=t^2+2t^3+3t^4 +4t^5+ \cdots +(n-1)t^{n}+nt^{n+1}.$$ Subtract, and rearrange a bit. We get $$(1-t)S(t)=(t+t^2+t^3+ +\cdots +t^n)-nt^{n+1}.\tag{$\ast$}$$ Recall that for $t\ne 1$, we have $t+t^2+t^3+ +\cdots +t^n=t\frac{1-t^n}{1-t}$.
If we do not recall the sum of a finite geometric series, we can find it by a trick similar to (but simpler) than the trick that got us to $(\ast)$.

Substitute, and solve for $S(t)$. (The method breaks down when $t=1$ because of a division by $0$ issue. But $t=1$ is easy to handle separately.)

Remark: Now that we have obtained an expression for $\sum{k=1}^n kt^k$, we can use this expression, and the same basic trick, to find $\sum_{k=1}^n k^2t^k$, and then $\sum_{k=1}^n k^3t^k$. Things get rapidly more unpleasant, and to get much further one needs to introduce new ideas.

share|improve this answer

Let $r=1/2$.

Write all the terms being added as $$ \left. \matrix{ r& \phantom{2}r^2& \phantom{2}r^3& \phantom{2}r^4&\cdots&\phantom{n}r^n \cr 0 & \phantom{2}r^2& \phantom{2}r^3& \phantom{2}r^4&\cdots& \phantom{2}r^n \cr 0&0& \phantom{2}r^3& \phantom{2}r^4&\cdots& \phantom{2}r^n\cr & \vdots&&&&\cr 0&0&0&0&\cdots& \phantom{2} r^n\cr }\ \ \right\} n-\text{rows} $$ $$ \overline{\matrix{ r&2r^2&3r^3&4r^4&\cdots&nr^n}\phantom{dfgfsdfsfs}} $$ Using the formula for the sum of a finite Geometric series, the sum of row $i$ is $$ r^i+r^{i+1}+\cdots+ r^n ={r^i-r^{n+1}\over 1-r }. $$

The sum of the row sums is $$\eqalign{ \sum_{i=1}^n {r^i-r^{n+1}\over 1-r } &= {1\over 1-r}\Bigl(\,\sum_{i=1}^n r^i- \sum_{i=1}^nr^{n+1} \Bigr)\cr &={1\over 1-r}\cdot \biggl({r-r^{n+1}\over 1-r}-nr^{n+1}\biggr)\cr &={1\over 1-r}\cdot \biggl({r-r^{n+1}\over 1-r}-{(1-r)nr^{n+1}\over1-r}\biggr)\cr &={ r-r^{n+1}-(1-r)nr^{n+1}\over (1-r)^2}\cr &={r-r^{n+1}(1+n-nr)\over (1-r)^2}. } $$

share|improve this answer

Hint: Consider $f(x) = \sum_{i=0}^n x^i$ as a function of $x$. This is a geometric series, so you can get a simpler expression for this:

$$\sum_{i=0}^n x^i = f(x) = \frac{1 - x^{n+1}}{1 - x}.$$

Now differentiating $f(x)$ with respect to $x$, we get

$$\sum_{i=1}^n i x^{i-1} = f'(x) = \left(\frac{1 - x^{n+1}}{1 - x}\right)' = \ \color{red}{?}$$

Multiplying everything by $x$ we get

$$\sum_{i=1}^n i x^i = x f'(x) = \ \color{red}{?}$$

Now plug in $x = \frac{1}{2}$ to get

$$\sum_{i=1}^n i \left(\frac{1}{2}\right)^i = \frac{1}{2} f'\left(\frac{1}{2}\right) = \ \color{red}{?}$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.